Influence of Sowing Date on Phenology, Biometric, and Yield of Mungbean (Vigna radiata) Cultivars in Chitwan, Nepal - Madhav Prasad Neupane; Hashmullah Musalman; Shrawan Kumar Sah (International Journal of Agronomy)
Mungbean is a commercially promising legume crop, accounting for a very low productivity of approximately 0.5 tons ha1 in the Terai region of Nepal. This study aimed to achieve the potential yield of mungbean promising cultivars planting at optimum sowing time. An experiment was conducted at the Agriculture and Forestry University (AFU), Rampur, Chitwan, during the spring of 2019 in a split-plot design (SPD) with three replications and 16 treatment combinations. Four sowing dates at 15 days intervals (13th February, 28th February, 15th March, and 30th March) of 2019; cultivars viz. Kalyan, Pratikshya, Pratigya, and Pant-5 are considered as main and subplot factors. The Dunken test was carried out to compare the mean in R-software at p≤0.05 level of significance. The results revealed that earlier planting (Feb 13 planting) resulted in delayed emergence, slower growth, and the lowest yield (1.79 tons/ha). The March 15 to March 30 plantations resulted in significantly faster emergence, germination, and growth showing a higher yield. Pant-5 yielded a higher grain yield, which was statistically at par with Partigya (2.08 tons/ha) and Partikshya (1.983 tons/ha). Vigna radiata plantations from March 15 to March 30 are the optimum sowing times for higher productivity (2.119 tons/hectare) and high potential yield, which can be applied for perfect decision-making in mungbean plantations. Future work on least-squares analysis for understanding the genotypic-environment interaction of economic traits and the effect of different nutrient sources on cultivars has scope.